The importance of colour on the communication of financial data in management. Issue 1 (24th July 2019) - Leong, Kelvin; Sung, Anna; Williams, Taylor; Andoniou, Costantine; Sun, Flora
Abstract : Purpose: The purpose of this paper is to explore the importance of colour on the communication of financial data in management and to encourage future discussion on related topic. Design/methodology/approach: Hypothesis was designed building on relevant literatures. Quantitative discrete data were collected through a mini-test activity in a lecture from students. The results were reviewed and evaluated by relevant statistical tool. Findings: The authors found consistent statistical significance results in the mini-test. The findings support that users prefer to choose the financial data presented in cool colours in business management context. Research limitations/implications: Gaining the understanding of colour's influence on decision making and behaviour is subjected to complexity. There are many other contextual factors should be taken into consideration in practice. Although the design of the mini-test in this study is relatively simple, it still provides clues for the issue. With the discussions and findings of this paper, the authors shed some light on the direction of potential uses of colour on the communication of financial data in management context. The findings could also be used by management educators to facilitate related discussions among students regarding the complexity of business communication and the importance of perception in decision making. For example, decision making could be affected by various factors (such as colour) outside verbal and text. Originality/value: Managers often need to use financial data in communication for various purposes in work place. The authors believe this is the first time that a study like this had been conducted to specifically review and discuss the importance of colour on the communication of financial data in management. Hopefully, the work reported in this paper could be viewed as reference for management educators, researchers and managers in future research or practical applications on related topics.